Scalloping is a reliable endoscopic marker for celiac disease. Issue 2 (9th June 2013) - Kasirer, Yair; Turner, Dan; Lerman, Leora; Schechter, Abraham; Waxman, Jacob; Dayan, Bosmat; Bergwerk, Ari; Rachman, Yelena; Freier, Zerem; Silbermintz, Ari
<x xml:space="preserve">Abstract</x> Background Scalloping of duodenal folds noted on esophagogastroduodenoscopy (EGD) has been associated with various illnesses including celiac disease (CD). The aim of the present study was to examine the frequency of scalloping in pediatric patients undergoing EGD and to assess its significance in the diagnosis of CD. We also evaluated the association of scalloping with the histopathology and celiac serology in the subgroup of celiac patients. Patients and Methods All children (0–18 years) who underwent EGD at Shaare Zedek Medical Center for any reason during a 2.5‐year period were retrospectively included, yielding a consecutive cohort without selection bias. Relevant data were obtained from the patient files. Results During the study period, 623 children underwent EGD of whom 149 (24%) were eventually diagnosed with CD. In 74/623children (12%), scalloping was seen and had a sensitivity of 48% (95% CI 0.40–0.57), specificity of 99% (0.98–0.99) and positive predictive value of 97% (0.9–0.99) to diagnose CD. The prevalence of scalloping increased with advancing stage of the Marsh classification from 33% (7/21) in Marsh 1 to 63% (34/54) in Marsh 3c (P < 0.001). Scalloping was associated with a significantly higher median tissue transglutaminase level (153 [IQR 98–168] versus 49 [IQR 11–143]; P = 0.011). Conclusion The results suggest that the diagnosis of CD is almost certain if isolated scalloping is observed during EGD done to rule out CD. Thus, attention to this finding may serve as an additional tool in the diagnosis of CD.